2019
DOI: 10.17984/adyuebd.495731
|View full text |Cite
|
Sign up to set email alerts
|

Kesirlerin Öğretiminde Artırılmış Gerçeklik Etkinliklerinin 5.sınıf Öğrencilerinin Matematik Başarılarına ve Tutumlarına Etkisinin İncelenmesi

Abstract: In the scope of the study, augmented reality activities for the fifth-grade mathematics were designed and administrated with students during mathematics lesson. Sixty, fifth grade, students from a middle school in Marmaris -Muğla participated to this study. This study was designed as pretest -posttest experimental research method without control group. An achievement test about fractions was applied as pre-test and post-test to students. In addition, Mathematics attitude scale developed by Aşkar (1986) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The students were socially involved in the learning process via the WhatsApp groups, and they also showed an increased interest. There are similar studies in the literature that have similar results (Chen, 2019 ; Fabian et al, 2018 ; Gecu-Parmaksiz & Delialioglu, 2019 ; Özdemir & Özçakır, 2019 ). The study of Fößl et al ( 2016 ) examined the effects of the mathematics seamless learning process on student success, concluding that the experimental group students showing better learning performances, and new learning and teaching environments were indicated as the reasons.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The students were socially involved in the learning process via the WhatsApp groups, and they also showed an increased interest. There are similar studies in the literature that have similar results (Chen, 2019 ; Fabian et al, 2018 ; Gecu-Parmaksiz & Delialioglu, 2019 ; Özdemir & Özçakır, 2019 ). The study of Fößl et al ( 2016 ) examined the effects of the mathematics seamless learning process on student success, concluding that the experimental group students showing better learning performances, and new learning and teaching environments were indicated as the reasons.…”
Section: Discussionsupporting
confidence: 58%
“…Augmented reality is a tool supporting students by filling the gaps between real-world situations and mathematical concepts using mathematical modeling (Cahyono et al, 2020 ). Augmented reality applications enable abstract concepts in mathematics teaching to be concretized through modeling or multiple displays (Özdemir & Özçakır, 2019 ; Zbiek & Conner 2006 ), and provides a better understanding of concepts (Bujak et al, 2013 ). However, it is stated that augmented reality applications usually target geometry in mathematics teaching and that there is a lack of subjects related to education and other learning areas of two-dimensional objects (Özdemir & Özçakır, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is seen that the results obtained from this study support the results of previous studies in the literature. It has been observed that the opinions on the theme"Contributions to mathematics learning" and the studies in the literature support each other.In the literature,studies are showing that success increased in mathematics courses where Metaverse technologies were used (Mutluoğlu & Erdoğan, 2021;Altıok, 2020;Özdemir & Özçakır, 2019;Şimşek et al, 2019), and students' attitudes towards mathematics (Özdemir & Özçakır, 2019) and geometry have changed positively (Mutluoğlu & Erdoğan, 2021), and that metaverse have positive effects on mathematics teaching-learning processes (Cabero-Almenara et al, 2021).It has been stated that integrating Metaverse into educational environments makes learning fun, engaging, and useful; increases the motivation of those who attend the course, and saves the course from mediocrity (Altıok, 2020;Çetin, 2019;Durak & Karaoğlan Yılmaz, 2019;Şimşek et al, 2019;İlic, 2013). Studies in the course show that using Metaverse technologies embodies abstract concepts, increases persistence (Lee et al, 2022;Boz & Özerbaş, 2020), frees the course from mediocrity, and increases self-efficacy of the participants (Şahin, 2016).…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…For example, Daghestani, Al-Nauim, Xu and Ragab (2012) demonstrated the use of a VR system representing a 3D-block array to enable young children to practice addition and subtraction numeracy concepts. An AR system, which demonstrated fractions, improved 5 th grade students’ achievements in this area and their attitude towards it (Özedmit & Özcakir, 2019). An AR system was also used to present geometrical objects to 8 th grade students (Cahyono, Sukestiyarno &Asikin, 2020) and fractions of objects and numbers in an immersive manner (Radu, McCarthy & Kao, 2016).…”
mentioning
confidence: 99%